The appearance of voice: EAP and academic literacies approaches to teaching reflective writing - Williams, Simon A. (Journal of Learning Development in Higher Education, 2019)
The increasingly common requirement for higher education courses to include reflective writing as part of assessment practices places additional demands on novice writers. Complex and self-referential assessment criteria mean that students on foundation and pre-sessional courses in particular find it hard to decode and match descriptors, and to balance subjectivity and critical analysis. English for Academic Purposes (EAP), the most widely adopted approach to teaching academic writing in higher education, prioritises objectivity, and teaches students to recognise generic patterns of text organisation – though it seldom includes reflective writing itself as a genre. In contrast, the less familiar teaching approach of academic literacies explores students’ subjectivity, more obviously relevant to reflection, often through the development of an authentic narrative voice. As in other forms of academic writing, voice in reflective writing can be seen as a construct. It conveys a persona via the narrative, and an ethos via its specialised content. However, unlike other forms of academic writing, the personain reflective writing must simultaneously communicate the author’s private and public self. With the purpose of developing students’ persona, an academic literacies intervention in two transition courses invited students to complete a piece of timed writing in response to an autobiographical prompt. Compared with the EAP writing produced by the same student cohorts, the autobiographical writing contained a clear persona and consistent ethos. The assessed reflective writing later produced by the same students showed little change, however, particularly in its handling of ethos. The findings suggest that teachers of reflective writing need simultaneously to develop students’ ability to communicate a credible persona and to handle a specialised ethos of formal academic content. A more principled combination of the two approaches, EAP and academic literacies, could best provide the optimum learning environment for novice student writers to develop a balanced voice and achieve reflective writing fluency